Effective Strategies for Teaching Pronunciation ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Pronunciation plays a crucial role in language acquisition, influencing effective communication. This article explores various strategies to enhance pronunciation teaching, focusing on practical approaches for educators and learners.